Antisocial Personality Disorder of Main Character The Invisible Man Movie Script by Leigh Whannel - Jadut, Citari Putri Patricia; Maca, Sudirman; Abeng, Andi Tenri (Humaniora: Journal of Linguistics, Literature, and Education, 2025)
This research aims to determine the characteristics of antisocial personality disorder experienced by the main character Adrian Griffin in the movie script The Invisible Man and also to determine the impact that Adrian's personality has on other characters. This type of research used a qualitative descriptive method. The data collection technique is carried out by reading, identifying and classifying words included in the film script. Based on the results and discussion, five characters were found in the Invisible Man film script based on Theodore Millons' theory: antisocial, passive aggressive. Sadistic, psychopath, histrionic and narcissistic. Of the five personalities found, Adrian's character dominates in antisocial behavior where he often ignores social norms, violates other people's rights and commits criminal acts without any sympathy at all for other people.